The The Effect of Leadership and Motivation on Employees Satisfaction: Evidence from Mirpur Division AJ&K in Restaurant Sector: The Effect of Leadership and Motivation on Employees Satisfaction: Evidence from Mirpur Division AJ&K in Restaurant Sector - Haroon Shakil (International Journal of Management Progress, 2020)
Governance mechanism has received high attention in previous year and has been a developing for research. This is mainly because of failure of number of firms in different regions. Good governance mechanisms are considered important in aspect of motivation, leadership and independent audit committee to increase the performance with the satisfaction of customers. These factors effect differently in developing and developed countries due to cultural, economic, social issues. The main objective of our research is to understand and determine the effect of governance mechanism on customer satisfaction in Mirpur division AJ&K. Despite the significance of our subject matter no prior research has focus on governance mechanisms in Mirpur division AJ&K. To accomplish the research objectives a quantities method (question was adopted). The questionnaire survey was used to seek the response of governance mechanism in aspect of motivation, leadership and independent audit committee from top level management and response of satisfaction received from customers. The data were analyzed using the statistical package for the social sciences (SPSS) to obtain quantities measure we use Pearson correlation, Mean, Standard deviation and regression. The finding of results shows that the customer satisfaction has positive relationship with motivation, leadership and independent audit committee. This study’s findings will also be beneficial to firms; government and policy maker as their political, social and economic environment are same.